UJI AKTIVITAS ANTIBAKTERI HASIL FRAKSINASI DARI EKSTRAK METANOL DAUN KATUK (Sauropus androgynus) TERHADAP BEBERAPA BAKTERI PATOGEN - Mukhriani Mukhriani; Nurshalati Tahar; Andi Sri Wahyuni Astha (Universitas Islam Negeri Alauddin Makassar, 2014)
Majority of traditional medicine uses herbal medicine to support health. Besides being able to cure the disease, traditional medicine also has side effects low or even non-existent. One of the plants used as traditional medicine is cinnamon leaf (Sauropus androgynous). Leaves widely used as a laxative breast milk for breastfeeding mothers. In addition, cinnamon leaf can be used as a drug for ulcerative lesions. This study aims to investigate the antibacterial activity of the methanol extract of leaves of cinnamon fraction (Sauropus androgynous). Characterization of compound akitif based thin-layer chromatography penampak various spots, including FeCl3, Dragendorf, Lieberman Buchard, ethanolic KOH, and Aluminum Chloride. Crude katuk leaves macerated using methanol for 3 days. The results showed that the methanol extract of cinnamon leaf has activity against the bacteria Salmonella and Staphylococcus aureus thyposa. Katuk leaf extract was fractionated by Vacuum Liquid Chromatography method. In this fractionation process, the eluent used was ethyl acetate and methanol (5:1). Results of fractionation of methanol extract in the form of a combined fraction of the number 6 keselurahan 14 fractions. Based on the TLC-profile Bioautografi fraction is the fraction of active 4 inhibits the growth of bacteria Salmonella and Staphylococcus aureus thyposa. From the results of the identification of the chemical components showed that compounds that inhibit the growth of bacteria on the 4th fraction are flavonoids.